Karakteristik Tenaga Kerja dan Pertumbuhan Ekonomi Terhadap Pengangguran Tenaga Kerja Terdidik di Indonesia - Agus Salim (FEB Universitas Sultan Ageng Tirtayasa, 2023)
This research was conducted to determine the effect of education, labor characteristics and economic growth on educated unemployment in Indonesia. The research data used is panel data for 34 provinces during the 2018-2022 period. The pooled regression analysis tool was chosen to determine the effect of education, labor characteristics and economic growth on educated unemployment in Indonesia. The conclusions of the research are; First, the higher the education, the greater the opportunity for workers to enter the labor market. Second, the labor characteristics including gender, marital status and experience contribute significantly to educated unemployment in Indonesia, and Thirdly, the economic growth achieved by each economy is a very important variable to reduce educated unemployment in their region.